Ligand-regulated peptide aptamers - Miller, Russell A (Methods in molecular biology (Clifton, N.J.), 2009)
The peptide aptamer approach employs high-throughput selection to identify members of a randomized peptide library displayed from a scaffold protein by virtue of their interaction with a target molecule. Extending this approach, we have developed a peptide aptamer scaffold protein that can impart small-molecule control over the aptamer-target interaction. This ligand-regulated peptide (LiRP) scaffold, consisting of the protein domains FKBP12, FRB, and GST, binds to the cell-permeable small-molecule rapamycin and the binding of this molecule can prevent the interaction of the randomizable linker region connecting FKBP12 with FRB. Here we present a detailed protocol for the creation of a peptide aptamer plasmid library, selection of peptide aptamers using the LiRP scaffold in a yeast two-hybrid system, and the screening of those peptide aptamers for a ligand-regulated interaction.